Assessing the Efficacy of Project-Based Learning in Higher Vocational English Courses for Developing Practical Communication Skills - Zhang, Yiyin; Li, Boli (Journal of Ecohumanism, 2024)
Aim: This research looks into how well Project-Based Learning (PBL) helps Chinese higher vocational college students to learn and communicate in real life. The main research question looks into how PBL, which includes incorporating the real world, learner-centered approaches, working with Chinese higher vocational college students from different fields, real-world assessment, and ongoing reflection, affects students’ oral communication, writing, critical thinking as well as intercultural communication abilities. Methodology: Systematic literature review was done, looking at English-language peer-reviewed papers from databases like PubMed, ERIC, Google Scholar, and PsycINFO to find out what effects PBL has on practical communication skills. The review included parts of PBL, such as, speaking and writing, critical thinking, active listening, and intercultural communication. It led to a comprehensive understanding of the way it affects English education at the higher vocaitonal education level. Results and Conclusions: The synthesized literature highlights the transformative influence of PBL on practical communication skills, emphasizing its role in fostering learner engagement, critical thinking, and adaptability in cross-cultural contexts. Oral communication, written expression, and interdisciplinary collaboration emerged as key domains positively influenced by PBL in the Chinese higher vocational education landscape. Recommendations: Teachers are advised to make using PBL methods a priority if they want to help Chinese higher vocational college students improve their speaking skills. This means creating a dynamic and collaborative learning space, encouraging collaboration across disciplines, and using real evaluations that are in line with learner-centered principles. Practical Implications: The study shows how PBL can be used in the real world to help Chinese higher vocational college students improve their communication, critical thinking, and ability to work with people from other cultures. The results support the use of PBL along with successful professional development programs to adapt to the changing needs of the globalized professional world.